Non‐electrolytic‐capacitor boost converter with non‐pulsating ripple‐free output current. (20th April 2021) - Zhang, Guidong; Chen, Weichen; Yu, Samson S.; Zhang, Yun
Summary: A novel boost converter is proposed in this study, which is based on a newly designed impedance network, instead of using the traditional Z‐network structure and large electrolytic capacitors (ECs) to suppress current ripples. Besides, the proposed topology has ripple‐free output current, which is designed to improve the output current quality of the traditional boost converter and to enhance the voltage conversion ratio compared to the traditional Z‐network boost converter. The newly proposed impedance network consists of two inductor and capacitor (LC) pairs—one LC pair function as the intermediate energy transferring branch and the other pair as the output branch to obtain non‐pulsating output current. The operating principle and performance of the proposed converter are analyzed in detail for demonstrating its advanced features. Furthermore, the feasibility of the proposed converter topology is validated by its simulations and experimental studies. Compared to ECs, non‐electrolytic capacitors (NECs) have the benefit of low cost, small size, and long operating life, which brings high economical advantages to the proposed converter with enhanced voltage conversion performances. Abstract : Key findings: A novel boost converter is proposed based on a newly designed impedance network, instead of using the traditional Z‐network structure and large electrolytic capacitors (ECs) to suppress current ripples. Besides, the proposed topology has ripple‐free output current to improve the output current quality and to enhance the voltage conversion ratio. ​